Leila or, the Siege of Granada, Complete - Lytton, Edward Bulwer Lytton, Baron, 1803-1873 (Salt Lake City, UT : Project Gutenberg, 2004)
"Leila or, the Siege of Granada, Complete" by Baron Edward Bulwer Lytton Lytton is a historical romance novel published in 1838. Set in Granada, Spain in 1491, the novel weaves together two parallel stories: the personal fate of Leila, a young Jewish woman caught between her heritage and forced conversion, and the historic siege that would end Muslim rule in Spain. Her father's shifting allegiances and desperate attempts to protect her lead to tragic consequences as Christian forces close in on the last Moorish stronghold. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Leila;_or,_The_Siege_of_Granada
Release date is 2004-11-27
Produced by David Widger
Keywords: Sieges -- Fiction; Granada (Spain) -- History -- Siege, 1491-1492 -- Fiction